Meme and Ideology: an Alternative Look of Analysis - Sánchez-Araya, Alejandro (2022)
This article focuses on a proposal for an alternative analysis of the meme, by transcending from “content” to “form”, based on the Evocation Model of Lee Wood, Stoltz, Van Ness and Taylor (2018) and the analytical theoretical perspective of the “Ideology” developed by Žižek (2003). Its purpose is to show that this type of cultural objects are made up of several layers, from which alternative readings can be generated. Through the methodological structure based on the social construction of meaning, the elements of the memes that work (from the žižekiana theory) will be identified as those symptoms that prevent the achievement of different ideological fantasies, based on the establishment of a common power pattern of character racialized. In this way, emphasis is placed on the reasons why the meme should be treated as a new cultural product governed by different visual codes and relationships whose interpellative capacity can be analyzed from its “form”.